2018
DOI: 10.1007/s10549-018-4990-9
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate machine learning models for prediction of pathologic response to neoadjuvant therapy in breast cancer using MRI features: a study using an independent validation set

Abstract: Purpose To determine whether a multivariate machine learning-based model using computer-extracted features of pre-treatment dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) can predict pathologic complete response (pCR) to neoadjuvant therapy (NAT) in breast cancer patients. Methods Institutional review board approval was obtained for this retrospective study of 288 breast cancer patients at our institution who received NAT and had a pre-treatment breast MRI. A comprehensive set of 529 radiomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 44 publications
1
133
2
1
Order By: Relevance
“…The optical model was able to perform robustly. Speci cally, the AUC of the nal model was 0.84, which was signi cantly higher than that of previous reports [12,25] based on the 1st phase. The result revealed that sequential texture features captured more detailed information of tumor complexity and heterogeneity that indistinguishable to the 1st phase.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…The optical model was able to perform robustly. Speci cally, the AUC of the nal model was 0.84, which was signi cantly higher than that of previous reports [12,25] based on the 1st phase. The result revealed that sequential texture features captured more detailed information of tumor complexity and heterogeneity that indistinguishable to the 1st phase.…”
Section: Discussioncontrasting
confidence: 66%
“…Whereas in uni-focal and unilateral multi-focal cases, the accuracy were 79% and 75% respectively. While in many studies [12,14,24,25], non-mass enhancement and unilateral multifocal cases were excluded, our model performed well without regarding to tumor morphology and number. Several studies suggested that non-mass enhancement and multifocal or multicentric [28][29][30] tumors were more frequently present in HER2positive subtype.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…11 Radiomics is the study of these quantitative features and their correlation with tumor phenotypes, 10 and it has been shown to be useful in predicting response to medical therapy in different tumor models. [12][13][14][15][16][17] In CRC correlation has been found between entropy and skewness, computed on CT scans, and tumor grade, KRAS mutational status and risk of recurrence in posttreatment future liver remnant. 18,19 However, prediction of the behavior of single lmCRC under treatment has not been explored and only one published study describes a machine learning method to predict treatment response of individual liver metastases from esophagogastric cancer, achieving an AUC of 0.87.…”
Section: Introductionmentioning
confidence: 99%